A importância dos mancais e rolamentos como elementos de máquinas - Silva, Robson de Oliveira (Brasil, 2022)
This work deals with the importance of bearings and bearings as machine elements for their perfect operation, and aims to describe concepts of bearings and bearings, to discuss their main types, characteristics and their use in each specific type of loads. Methods for its better functioning and extension of its useful life, always recommending its use according to the specifications of its manufacturers. In this work, the research model used was qualitative, with bibliographical research, addressing research already done on the subject, such as specific catalogs of manufacturers, university articles, manufacturers' websites, university handouts, books and course completion work . The research aimed to clarify technical knowledge about bearings and bearings in order to improve scientific knowledge about these elements of machines. Through this it was possible to observe on what occasions each bearing and bearing should be best used.